Prognostic and clinicopathological significance of Fusobacterium nucleatum in colorectal cancer: a systemic review and meta-analysis - Younghoon Kim; Nam Yun Cho; Gyeong Hoon Kang (Journal of Pathology and Translational Medicine, 2022)
Background Fusobacterium nucleatum has been identified to promote tumor progression in colorectal cancer (CRC). However, association between F. nucleatum and prognostic or clinicopathological features has been diverse among studies, which could be affected by type of biospecimen (formalin-fixed paraffin-embedded or fresh frozen [FF]). Methods Articles were systemically reviewed for studies that included the correlation between F. nucleatum and prognosis or clinicopathological features in CRC. Results Ten articles, eight studies with survival-related features involving 3,199 patients and nine studies with clinical features involving 2,655 patients, were eligible for the meta-analysis. Overall survival, disease-free survival, and cancer-specific survival were all associated with worse prognosis in F. nucleatum–high patients (p<.05). In subgroup analysis, only studies with FF tissues retained prognostic significance with F. nucleatum. In meta-analysis of clinicopathological variables, F. nucleatum level was associated with location within colon, pT category, MLH1 hypermethylation, microsatellite instability status, and BRAF mutation regardless of type of biospecimen. However, lymph node metastasis and KRAS mutation was only associated with F. nucleatum level in FF-based studies. Conclusions In conclusion, type of biospecimen could affect the role of F. nucleatum as a biomarker associated with clinicopathological features and prognosis.